IoT-Based Safety Baby Car Seat with Mobile Application - Mohd Faizal, Ahmad Farhan; Mohamad, Shamsul (Evolution in Electrical and Electronic Engineering, 2025)
Forgotten Baby Syndrome (FBS), where caregivers accidentally leave babies in cars, can have fatal consequences. This IoT-Based Safety Baby Car Seat with Mobile Application project is designed to prevent such tragedies. Leveraging IoT technology, the system enables real-time monitoring, alert notifications, and data analysis to enhance the safety of baby car seats. It features sensors to detect a baby’s presence by detecting weight on a seat and monitoring environmental conditions, such as temperature and humidity inside the vehicle. The collected data is securely transmitted to a cloud platform for analysis. When hazardous conditions are identified, such as an unattended baby or extreme temperatures, the system triggers alerts via the Blynk Application and activates car ventilation to maintain safe conditions. The testing results demonstrated the system’s effectiveness in gaining an accurate, fast response every time it was executed to ensure reliable performance. However, the alert notification depends on the weather and temperature outside. This innovative approach improves child safety and provides caregivers peace of mind through continuous monitoring and rapid responses. The project represents a significant advancement in ensuring safer travel for babies.